تداعيات الأزمة السورية على قطاع النقل السككي ودوره في إعادة الإعمار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يدرس هذا البحث تأثير الأزمة السورية على قطاع النقل السككي والدور الذي يمكن أن يلعبه النقل السككي في عملية إعادة إعمار سورية, وتطرح مشكلة البحث التساؤلات الآتية: ما هو حجم الضرر الذي لحق بالنقل السككي جراء الأزمة السورية؟, وما الدور الذي يمكن أن يؤديه النقل السككي في تحفيز عمليات النمو الاقتصادي وتسريع وتيرة إعادة إعمار ما دمرته الحرب الكونية على سورية؟, حيث تركزت أهداف البحث على دراسة أهمية النقل في تنمية الاقتصاد الوطني وتطور ايرادات النقل السككي خلال عدة أعوام لما قبٍل الأزمة وما بعدها, و توصل الباحث إلى عدة نتائج منها: تأثر وتضرر قطاع النقل بشكل كبير جراء الأزمة, وتوقف النقل السككي في أغلب المناطق نتيجة الأعمال الإرهابية وقطع الطرقات وتدمير القاطرات والأبنية والبنى التحتية لشبكة الخطوط الحديدية, وأيضاً زيادةٍ نسبة إسهام النقل السككي بالنسبة للنقل العام خلال الازمة وخاصة بالفروع القريبة من الموانئ والمناطق الآمنة. خلص الباحث إلى عدة توصيات منها: ضرورة الإسراع ببناء المرافئ الجافة, وضرورة إعادة صيانة وتطوير شبكة النقل السككي من أجل زيادة مساهمتها في تأمين الخدمات اللوجستية الضرورية لإعادة الإعمار, إضافة إلى المساهمة الفعالة في تأمين مصادر التمويل لإعادة الاعمار. This research studies the impact of the Syrian crisis on the railway transport sector and the role that can be played by the railway transportation in the reconstruction process of Syria. The problem of this research leads us to ask the following questions: what is the extent of damage to the railway transport sector caused by the Syrian crisis?, what are the role and effect that can be played by railway transport in stimulating economic growth and accelerating the of reconstruction what was destroyed by the global war on Syria. The objectives of the research were to study the importance of transportation in the development of the national economy and the development of the revenues of railway transport during several pre-crisis and post-crisis years. The researcher reached several results including: the transportation sector has been severely affected and damaged in most areas, railway transport has ceased as a result of terrorist acts, roadblocks and the destruction of locomotives buildings and infrastructure of the rail network, And also the contribution of rail transport to public transport increased during the crisis especially in the branches near the ports and regions. The researcher concluded several recommendations including: The need to expedite the construction of harbors, and the need to develop the railway network in order to increase its contribution in securing the necessary logistic services to restriction, as well as to contribute effectively to securing sources of funding for the reconstruction.